Adsorption-reduction of Cr(VI) onto unmodified and phytic acid-modified carob waste: Kinetic and isotherm modeling. (June 2022) - Bouaouina, Kenza; Barras, Alexandre; Bezzi, Nacer; Amin, Mohammed A.; Szunerits, Sabine; Boukherroub, Rabah
Abstract: Carob waste (CW) is an agro-biomass material abundant in nature with potential use for eco-friendly remediation. However, like many biomass-based adsorbents, it suffers from its low adsorption capacity for organic/inorganic pollutants. Therefore, modification using physical and/or chemical means is commonly applied to improve the adsorptive properties of biomass-based adsorbents. In this study, carob waste (CW) and carob waste functionalized with phytic acid (PA-CW), as an ecofriendly product, were applied for the first time for Cr(VI) elimination. Various methods were applied for the material characterization like Fourier-transform infrared spectroscopy, powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA and DTG), X-ray photoelectron spectroscopy (XPS), specific surface area and porosity measurements. The results proved that both CW and PA-CW own appropriate features for efficient adsorption. Bach experiments revealed that the optimum parameters for Cr(VI) (100 mg/mL) removal at 25 °C were pH 2, 0.05 and 0.025 g as adsorbent dose for CW and PA-CW, respectively, over 120 min contact time. The kinetic of adsorption was well-described by the pseudo-second order model, whereas the isotherm modeling fitted well the modified Langmuir model. CW and PA-CW achieved respectively maximum adsorption capacities of 212.4 and 387.9 mg/g, which are among the highest values so far reported for biomass-based adsorbent materials. These results confirmed that CW and PA-CW could be alternative cost-effective adsorbents even for high concentrations of Cr(VI) in industrial wastewaters along with their reduction capacity. Graphical abstract: Image 1 Highlights: Carob waste was investigated as a low-cost adsorbent. Modification of carob waste using phytic acid as an eco-friendly agent. Adsorption capacity of Cr(VI) increased from 243.9 to 434.8 mg/g after modification. Reduction of Cr(VI) to Cr(III) during the adsorption process.